Investigating the Meat Pathway as a Source of Human Nontyphoidal Salmonella Bloodstream Infections and Diarrhea in East Africa. (10th August 2020) - Crump, John A; Thomas, Kate M; Benschop, Jackie; Knox, Matthew A; Wilkinson, David A; Midwinter, Anne C; Munyua, Peninah; Ochieng, John B; Bigogo, Godfrey M; Verani, Jennifer R; Widdowson, Marc-Alain; Prinsen, Gerard; et al.
Abstract: Background: Salmonella Enteritidis and Salmonella Typhimurium are major causes of bloodstream infection and diarrheal disease in East Africa. Sources of human infection, including the role of the meat pathway, are poorly understood. Methods: We collected cattle, goat, and poultry meat pathway samples from December 2015 through August 2017 in Tanzania and isolated Salmonella using standard methods. Meat pathway isolates were compared with nontyphoidal serovars of Salmonella enterica (NTS) isolated from persons with bloodstream infections and diarrheal disease from 2007 through 2017 from Kenya by core genome multi-locus sequence typing (cgMLST). Isolates were characterized for antimicrobial resistance, virulence genes, and diversity. Results: We isolated NTS from 164 meat pathway samples. Of 172 human NTS isolates, 90 (52.3%) from stool and 82 (47.7%) from blood, 53 (30.8%) were Salmonella Enteritidis sequence type (ST) 11 and 62 (36.0%) were Salmonella Typhimurium ST313. We identified cgMLST clusters within Salmonella Enteritidis ST11, Salmonella Heidelberg ST15, Salmonella Typhimurium ST19, and Salmonella II 42:r:- ST1208 that included both human and meat pathway isolates. Salmonella Typhimurium ST313 was isolated exclusively from human samples. Human and poultry isolates bore more antimicrobial resistance and virulence genes and were less diverse than isolates from other sources. Conclusions: Our findings suggest that the meat pathway may be an important source of human infection with some clades of Salmonella Enteritidis ST11 in East Africa, but not of human infection by Salmonella Typhimurium ST313. Research is needed to systematically examine the contributions of other types of meat, animal products, produce, water, and the environment to nontyphoidal Salmonella disease in East Africa. Abstract : The meat pathway may be an important source of human invasive Salmonella Enteritidis ST11 infections in East Africa, but not of Salmonella Typhimurium ST313. Improvements to meat safety are warranted while research on sources for other nontyphoidal Salmonella infections continues.